Reading Habits and Information Access in the Digital Age: A Case Study at Kwara State University Nigeria - Abubakar, Jemilat Biogera; Utami, Ari Mulya (Indonesian Journal of Librarianship, 2024)
Background: Traditional information access and retrieval of the young generation have changed and will continue to change with the digital revolution of today’s world. People, especially the young digital generation, called Netizens, more often than not, read contents in electronic mode causing a new revolution in the information access. Technological affordances such as the cost, technical know-how among others make such change very difficult and exhausting. In view of these, it is imperative to carry out this investigation which aims to provide background of the concept of reading and information access as well as netizens, it expounds the internet culture and the availability of overwhelming online content and tools for the information seekers. Purpose: To expounds the internet culture and the availability of overwhelming online content and tools for the information seekers. Method: The case-study research design was adopted for this study, the sampling method adopted in this study is the simple random sampling technic and question was adopted as the primary data collection instrument. Result: The study revealed that most of the internet facilities such as World Wide Web, and File Transfer Protocol were not used for learning by finalists of the faculty of ICT, Kwara State University, Malete.The findings revealed that the internet facilities available are only applied to reading and writing and not to other learning activities. The study also discover that the extent of internet application to learning is great in Kwara State University, Malete. Conclusion: This study concludes that the reading habits and information access of students in the ICT Faculty at Kwara State University are still lacking. The study recommends a balance between digital acceleration and traditional print information sources. Students' reading habits and information access can be improved by effectively using the internet. To dramatically enhance the quality of graduates and the standards of higher education, universities in Nigeria need to continue expanding access to internet information sources by providing the necessary basic facilities for effective connectivity.